2022
DOI: 10.1093/sleep/zsac289
|View full text |Cite
|
Sign up to set email alerts
|

Craniofacial phenotyping by photogrammetry in Chinese prepubertal children with obstructive sleep apnea

Abstract: Study Objectives This study aimed to examine the craniofacial phenotype of Chinese prepubertal children with and without OSA using a quantitative photographic analysis technique and to develop a prediction model for OSA diagnosis based on the photogrammetric data. Potential ethnic differences in the association between OSA and photogrammetric data between Chinese and Caucasian children were also examined. Methods This was a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“… 59 Yuen found significant differences in the maxillary-mandibular relationship angle and the ratio of mandibular height to the entire length of the face in prepubertal children as the severity of OSA increased. 33 The model established by Masoud through three-dimensional airway analysis shows remarkable predictive value. 60 In summary, the use of craniofacial anthropometry and photogrammetry to assess facial features has been proposed as an alternative technique for OSA in both adults and children, and very low to moderate quality levels of data, have not been able to support the existence of an association, or lack thereof, between craniofacial morphology and pediatric OSA.…”
Section: Discussionmentioning
confidence: 99%
“… 59 Yuen found significant differences in the maxillary-mandibular relationship angle and the ratio of mandibular height to the entire length of the face in prepubertal children as the severity of OSA increased. 33 The model established by Masoud through three-dimensional airway analysis shows remarkable predictive value. 60 In summary, the use of craniofacial anthropometry and photogrammetry to assess facial features has been proposed as an alternative technique for OSA in both adults and children, and very low to moderate quality levels of data, have not been able to support the existence of an association, or lack thereof, between craniofacial morphology and pediatric OSA.…”
Section: Discussionmentioning
confidence: 99%
“…The different cutoff values may influence the results. However, based on the recommendations of ICSD-3 and most researchers, we deemed it more appropriate to use the current cutoff value (51)(52)(53)(54)(55).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, prolonged mouth breathing gradually stretches the child’s head and neck forward, increasing the anterior craniocervical angle [ 15 , 16 ]. The angle between the mandible and maxilla rises sharply as OSAHS severity increases, and the proportion of anterior mandibular height to total face length considerably declines [ 17 ]. Motta et al reported craniocervical postural abnormalities in children with SB using digital photogrammetry [ 18 ].…”
Section: Introductionmentioning
confidence: 99%